Protein Tyrosine Phosphatase SHP-2 Is Positively Involved in Platelet-Derived Growth Factor-Signaling in Vascular Neointima Formation via the Reactive Oxygen Species-Related Pathway - Kyung-Jong Won; Hwan Myung Lee; Chang-Kwon Lee; Hai Yue Lin; Haerang Na; Ki Won Lim; Hui Yul Roh; Seobo Sim; Hyuk Song; Wahn Soo Choi; Seung Hyun Lee; Bokyung Kim (Elsevier, 2011)
The roles of Src homology domain 2-containing protein tyrosine phosphatase 2 (SHP-2) and its signaling in atherosclerosis have not been explored. Therefore, we investigated the roles of SHP-2 in the movement of rat aortic smooth muscle cells (RASMCs) and in the neointima formation of the carotid artery. Platelet-derived growth factor (PDGF)-BB (1 − 20 ng/ml) increased the activity and phosphorylation of SHP-2 and migration in RASMCs and these were suppressed by SHP-2 inhibitor NSC-87877 (30 μM) and small interfering RNA of SHP-2. PDGF-BB increased the phosphorylations of spleen tyrosine kinase (Syk) and p38 mitogen-activated protein kinase (MAPK), which were recovered by inhibition of SHP-2. Moreover, PDGF-BB increased the levels of reactive oxygen species (ROS) and ROS inhibitors decreased PDGF-BB-increased migration. Treatment of RASMCs with H2O2 (100 μM) increased cell migration and SHP-2 phosphorylation and also enhanced the phosphorylation levels of Syk and p38 MAPK. Oral administration of NSC-87877 (10 mg/kg) significantly suppressed neointima formation in a rat model of carotid artery injury. These results suggest that the activity of SHP-2 is controlled by ROS and is positively involved in the regulation of PDGF-BB-induced RASMC migration and neointima formation. Keywords:: SHP-2, reactive oxygen species (ROS), platelet-derived growth factor (PDGF)-BB, vascular remodeling, migration